1990
DOI: 10.1016/s0022-5347(17)40177-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Streptozotocin-Induced Diabetes on Bladder Function in the Rat

Abstract: Streptozotocin-induced (STZ, 60 mg./kg. I.V.) diabetic male rats underwent cystometrographic (CMG) and electrophysiologic evaluations under urethane anesthesia (1.2 gm./kg.) to determine whether the neural pathways to the urinary bladder are altered in these animals. Diabetic rats (n = 6) in comparison to controls (n = 8) had significantly greater micturition volumes (3.0 +/- 0.8 ml. vs. 0.7 +/- 0.4 ml., p less than 0.001), bladder compliances (0.51 +/- 0.15 cm. H2O/ml. vs. 0.12 +/- 0.09 cm. H2O/ml., p less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
3
21
0
4
Order By: Relevance
“…In practice, the functional studies in STZ rat model have demonstrated a relationship between polyuria and alterations in bladder volume, rate of filling, and bladder stretching. Increased bladder work and distension leads to progressive remodeling and deterioration of the bladder 35, 36…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the functional studies in STZ rat model have demonstrated a relationship between polyuria and alterations in bladder volume, rate of filling, and bladder stretching. Increased bladder work and distension leads to progressive remodeling and deterioration of the bladder 35, 36…”
Section: Discussionmentioning
confidence: 99%
“…This suggests deficits in the upstream neuronal pathways innervating the urethra. In support for this, histological (size of cell bodies), neurochemical (reduction of Substance P, increase in NGF, and other peptides) and functional (ion channels) alterations in the primary afferent neurons in the dorsal root ganglia and/or efferent neurons in the major pelvic ganglia have been previously reported (Santicioli et al, 1987;Steers et al, 1990Steers et al, , 1994Sasaki et al, 2002;Yang et al, 2008). In addition, recent findings investigating synaptic transmission in the major pelvic ganglion of the obese type 2 diabetic mice identified altered pre-synaptic regulation of transmitter release (Tompkins et al, 2013).…”
Section: Discussionmentioning
confidence: 61%
“…Morphological, histological and functional alterations in autonomic neurotransmission have been reported in diabetes [9]. In addition, there is evidence that diabetes is associated with increased bladder weight [12]. This is thought to be secondary to diabetes-induced diuresis, which, in turn, leads to increased bladder weight [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence that diabetes is associated with increased bladder weight [12]. This is thought to be secondary to diabetes-induced diuresis, which, in turn, leads to increased bladder weight [12]. The increase in bladder weight has, in itself, been attributed to increased cellular proliferation, in particular, urothelial cell proliferation [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation